Abstracts - Journal Editors (مجلة (اعلم), 2023)
Saudi universities standings in the international rankings of universities: Information Science view Saad Ahmed Alzahrani This study sought to identify the standing of the Saudi universities in the most famous international university rankings; Shanghai Academic Ranking of World Universities (ARWU) - Webometrics Ranking of World Universities (WRWU) – QS World university Ranking - ranking of global institutions by SCImago. An analysis was conducted of the criteria and indicators to each ranking system also we presented the weaknesses of each ranking system. The study concluded that the history of the emergence of international rankings of universities dates back to the late nineteenth century, specifically 1983 in the United States of America, and that the ranking of Saudi universities varies from one classification to another according to the methodology, criteria and indicators of each classification. The study also proved that the QS classification is one of the most famous classifications in terms of diversity and inclusion, taking into account the cultural diversity and the surrounding environment of universities. The classification provides criteria and indicators for the classification of universities worldwide in general, and for universities in Asia, Latin America and the Arab world separately, with some relatively different criteria and weights. The study confirmed that there is a strong relationship between the global rankings of universities and the field of libraries and information science. The Shanghai classification system is the most relevant classification in the field of libraries and information, accounting for 60% of the total classification indicators and weights. The study also proved that King Abdulaziz University topped the list of Saudi universities in both the Shanghai ranking, the QS ranking, and the Times ranking, which confirms the activity of King Abdulaziz University and its relentless pursuit to achieve a distinguished position among the Universities of the world. While King Saud University topped the list of Saudi universities in the Webometrics ranking and King Abdullah University of Science and Technology topped the list of Saudi universities in the SCImago research ranking. Finally, the researcher put forward a set of proposals and mechanisms to improve the standings of Saudi universities in ranking systems. The Importance of Scientific Research Methods and Methods Courses in Forming Research Skills: For Students in the Information Studies Department - Libyan Academy Hanan Al-Sadiq Bizan The reality is that the development and progress of human societies depends on scientific research in all fields. Through concerted efforts, knowledge accumulation takes place, as higher and university education institutions are considered academic institutions located at the top of the educational pyramid, and play a leading role and great responsibility in forming and refining skills and capabilities. Research, the development of intellectual capital and technological progress, with the natural balance between preserving self-identity and openness to the global knowledge community. In this regard, scientific research is considered an organized method from collecting reliable information to taking notes and objective analysis of that information, by following specific scientific methods and approaches with the intent of ascertaining its validity or modifying and adding new ones to it, and then arriving at new facts, laws and theories. Perhaps in the context of this, the problematic of this research paper is embodied through the researcher’s repeated observation in recent years, the delay and stumbling block of many students studying in the Department of Information Studies in preparing research plans for the "Master’s". In this context, the study mainly aims to reach an answer to the following question: The extent to which the courses of research methods and methods in particular, and the rest of the curricula in general benefit on the abilities and skills of students studying in the stage of preparation for a master’s research (preparation of a proposal) in the Department of Information Studies?. Components of knowledge management in business institutions and their role in activating knowledge investment: a scientific review Essa Alluhaybi & Abdulrahman Alqarni Modern organizations in the era of the knowledge economy have enjoyed the elements of knowledge management in order to achieve effectiveness and efficiency in the work entrusted to them and at the same time organizations have faced accompanying current developments towards investing in the elements of knowledge management that contribute to achieving their goals, moreover organizations are working through the strategy of business practices and changing conditions in the work environment towards building new practices to reduce the continuous and dynamic development in the work environment that ensures that organizations remain in the circle of competition with international organizations It enables them to respond and adapt continuously to support future strategies. Perhaps in this scientific model, we have touched on the elements of knowledge management in business organizations and their role in activating knowledge investment through the main question through the use of a model of literature review to present a set of studies related to the variables of the study, and the results showed that the elements of knowledge management contribute to the success of organizations’ investment of their resources, and lie in that they have an impact on attracting investors, increasing products and improving services. The current study found that the elements of knowledge management are the basis for gaining the competitive advantage of the organization through its management of effective investments of organizations through increasing the utilization of internal knowledge assets and the integrated view of coordinating the various activities of the organization towards achieving its objectives. Research trends of theses in Egyptian universities in orphan research Abdullah Almehdar The issue of orphans is of utmost importance in all fields and specializations. It has branching relationships with many sciences, and interest in it is considered a religious, moral, social, and scientific matter as well. The main objective of the study revolved around documenting scientific theses in Egyptian universities in orphan research, and several objectives branched out from it, including analysing the numerical and qualitative characteristics of scientific theses in Egyptian universities that were conducted on orphan topics and identifying research trends in the fields of orphans. The study relied on the bibliometric approach to analyse the characteristics of theses and their various trends, after inventorying them as a first step through searching the scientific theses database of the Egyptian University Libraries Federation and based on a codified form for collecting data. The study concluded with several results, the most important of which are: that the number of master’s theses reached (152) with a percentage of (76%), and doctoral theses (48) with a percentage of (24%), and that there was a noticeable increase in the number of research papers that reached a peak in 2017, it was 13.5%, then it gradually decreased. The largest share of scientific theses, at a rate of more than 30%, was for the specializations of the faculties of social sciences, with a scarcity of scientific theses in the field of laws and legislation, as well as multidisciplinary dissertations (interdisciplinarity). It was found that there was a statistical significance for the academic degree variable on the variables (study topics, sample selection methods, data collection tools) in favour of the doctoral sample, while there was no statistical significance for the academic degree variable on the variables (study population, study methodology, study sample). What the study recommended was to benefit from its results in developing the research plan of the Al-Issa Chair for Orphan Research and other scientific bodies to cover the research gaps that were monitored, considering their compatibility with Vision 2030, and the necessity of developing research priorities in academic departments to serve societal issues, including those related to orphans, in addition to establishing a base. Specialized data on orphans and all fields related to them and their sponsoring and donor institutions. Extracting knowledge from customer experiences: A review of the topic literature and research directions. EMAN JARY ALMETIRY The topic literature review aimed to cover the published literature on the topic of extracting knowledge from customer experiences and to illustrate the beginning and development of studies in the topic. To search for intellectual production in the Arabic language, three databases were searched: Dar Al Manzma database for scientific letters and periodicals, Economics and Management Information database, Ecolink, and Google Scholar search engine in Arabic. and to search for intellectual production in English, three databases were searched: the IEEE database; Proquest Base (Thesis and Dissertations), Google Scholar search engine in English. The review reached a set of results, the most important of which is that the interest in the subject of knowledge extraction and the customer experience began in the early nineties, based on what was published in the intellectual production, which was limited and studied. 20004 AD. By researching the intellectual production published in the English language, it was found that the term “knowledge extraction” was the most used, followed by the term “customer experience,” in contrast to the Arab intellectual production, where the results showed a scarcity of use of the term. The literature review of the subject also showed the lack of Arabic studies, conferences and workshops that dealt with the subject of knowledge extraction and the subject of the customer experience, and no paper appeared that dealt with the subject of extracting knowledge from customer experiences, which shows the necessity of enriching intellectual production in the field of knowledge extraction and the scientific addition provided by this review in the field.